Experimentación con herramientas y materiales reciclados utilizados en artes plásticas para la creación de objetos artísticos, en los habitantes de la parroquia Licto, barrio Chimbacalle, en el período 2021-2022 - Puli Espinoza, Jessica Natalia (2022)
The plastic arts were the maximum expression of the human being, it interacted with the appropriation of knowledge and the perception of life. Nowadays the art seeks the conservation of the environment itself that will guarantee the use of natural resources. The purpose of this research was the creation of artistic objects through recycled tools and materials, in this way the conservation of the environment is encouraged. We worked with children, young people and adults from the Chimbacalle neighborhood of the Licto Parish through the application of instruments that allowed to identify knowledge about plastic arts. The methodology was descriptive, bibliographic and field. One of its conclusions allowed to demonstrate the adequate applicability of recycled tools and materials in the generation of artistic objects and the stimulation of creativity and mental development of children, young people and adults.